Colitis possibly induced by quetiapine. (26th February 2015) - de Beaurepaire, Renaud; Trinh, Isabelle; Guirao, Sophie; Taieb, Muriel
Abstract : A 39-year-old man with bipolar disorder was hospitalised for depression. He was started on quetiapine (titrated up to 300 mg), lactulose (a laxative) and tropatepine (an anticholinergic). Valpromide (a mood stabiliser) and prazepam were later added and rapidly withdrawn. Seven days after quetiapine initiation, the patient reported abdominal pain and constipation; 2 days later, CT revealed an important distention of the colon including the caecum and a pre-perforation. A subtotal colectomy was performed and histology confirmed necrotising ischaemic colitis. The patient survived. This is the first case reported so far of ischaemic colitis related to quetiapine, in the absence of other antipsychotics simultaneously prescribed. Tropatepine likely acted as a cofactor to determine colitis. Clinicians need to be aware of the potential danger of the co-prescription of quetiapine with tropatepine (and possibly other anticholinergics).